From salty to thriving: plant growth promoting bacteria as nature’s allies in overcoming salinity stress in plants - Peng, Mu; Jiang, Zhihui; Zhou, Fangzhen; Wang, Zhiyong (Frontiers in Microbiology, 2023)
Soil salinity is one of the main problems that affects global crop yield. Researchers have attempted to alleviate the effects of salt stress on plant growth using a variety of approaches, including genetic modification of salt-tolerant plants, screening the higher salt-tolerant genotypes, and the inoculation of beneficial plant microbiome, such as plant growth-promoting bacteria (PGPB). PGPB mainly exists in the rhizosphere soil, plant tissues and on the surfaces of leaves or stems, and can promote plant growth and increase plant tolerance to abiotic stress. Many halophytes recruit salt-resistant microorganisms, and therefore endophytic bacteria isolated from halophytes can help enhance plant stress responses. Beneficial plant-microbe interactions are widespread in nature, and microbial communities provide an opportunity to understand these beneficial interactions. In this study, we provide a brief overview of the current state of plant microbiomes and give particular emphasis on its influence factors and discuss various mechanisms used by PGPB in alleviating salt stress for plants. Then, we also describe the relationship between bacterial Type VI secretion system and plant growth promotion.